Discrepancies between children's and caregivers' child maltreatment reporting and their associations with child wellbeing. (November 2022) - Zhang, Saijun; Xu, Yanfeng; Hong, Jun Sung; Liu, Meirong; Liao, Minli
Abstract: Background: Child maltreatment reporting is critical for case investigation and service disposition. However, reporting discrepancies across informants is a challenge for child welfare services. Methods: Using data from the Fragile Families and Child Wellbeing Study ( n = 3150), the current study examined child-caregiver discrepancies in reporting the frequencies of psychological and physical maltreatment. Multivariate models were used to examine how caregivers' reports, children's reports, and discrepancies between the two were associated with child anxiety, depression, aggression, and delinquency. Results: A quarter of the children reported psychological maltreatment at a higher (25.7 %) or lower (23.8 %) frequency than their caregivers' report, respectively; 8.4 % and 8.7 % of the children did so in physical maltreatment reports, respectively. Multivariate models showed that children's maltreatment reports were more closely associated with children's anxiety, depression, and delinquency than caregivers' reports, while caregivers' reports were more closely associated with children's aggression. After accounting for caregivers' reporting and other covariates, children who reported more frequent psychological maltreatment than their caregivers' report had a higher level of anxiety, depression, and delinquency ( b = 0.17 to 0.25, p < 0.001), and the opposite was true ( b = −0.36 to −0.13, p < 0.001). Similarly, children who reported more frequent physical maltreatment than their caregivers' report had a higher level of all negative outcomes ( b = 0.04 to 0.44; p = 0.04 to <0.00), and the opposite was true for aggression ( b = −0.08, p = 0.004). Conclusions: The findings suggest that in addition to other reporting barriers, children and caregivers may perceive maltreatment differently, and such discrepancies are related to children's wellbeing.